2020
DOI: 10.1007/s00420-020-01537-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of lung cancer in Canada attributed to occupational radon exposure using a novel exposure assessment method

Abstract: Objective Exposure to radon causes lung cancer. The scope and impact of exposure among Canadian workers have not been assessed. Our study estimated occupational radon exposure in Canada and its associated lung cancer burden. Methods Exposed workers were identified among the working population during the risk exposure period (1961-2001) using data from the Canadian Census and Labour Force Survey. Exposure levels were assigned based on 12,865 workplace radon measurements for indoor workers and assumed to be 1800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Radon-attributable lung cancer deaths for all 66 countries totaled 226,057 in 2012 and represented a median of 3.0% of total cancer deaths [77]. Recently, multiple published studies have measured the risk of developing lung cancer following residential or occupational radon exposure in various regions of the world, as well as the synergistic effect of cigarette smoking and the effect in never-smokers [8][9][10]73,[77][78][79][80][81] as well as analyzing the histological types of lung cancer [82].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
“…In the near future, a study of the annual urban radon average will be conducted with the newly studied monitoring system, and appropriate measures addressing radon should be undertaken in areas of increased exposure to this noble gas to obtain longitudinal analyses of the risk of populations resulting from indoor radon exposure [73]. Monitoring the exposure of resident populations is relevant in light of the small lung cancer burden associated with occupational radon, with the greatest burden occurring among those exposed to low levels of radon [8,80,[85][86][87].…”
Section: Radon-attributable Lung Cancer Riskmentioning
confidence: 99%
“…While greater lung cancer risk is associated with increasing level of radon exposure 7 , no safe level of radon exposure exists 37 , and studies have reported positive associations between relatively low indoor radon concentrations and lung cancer risk 8 . CAREX Canada’s exposure estimates for 2006 were previously applied to estimate the burden of lung cancer cases associated with occupational radon exposure in Canada 38 – 40 . The results showed that while there is a relatively small lung cancer burden associated with occupational radon exposure overall (0.8% of lung cancers were attributable to occupational radon exposure, compared to 17.5% for tobacco smoking, and 0.8% for second-hand tobacco smoke exposure 41 ), low level exposures accounted for the majority of the burden 38 .…”
Section: Discussionmentioning
confidence: 99%
“…CAREX Canada’s exposure estimates for 2006 were previously applied to estimate the burden of lung cancer cases associated with occupational radon exposure in Canada 38 – 40 . The results showed that while there is a relatively small lung cancer burden associated with occupational radon exposure overall (0.8% of lung cancers were attributable to occupational radon exposure, compared to 17.5% for tobacco smoking, and 0.8% for second-hand tobacco smoke exposure 41 ), low level exposures accounted for the majority of the burden 38 . Of the 188 lung cancer cases attributable to occupational radon exposure during the risk exposure period (1961–2001), 139 cases (or 74%) were associated with radon levels less than 200 Bq/m 3 due to the very large size of the population exposed at this level 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation